Effect of Quadruple Regimen with Lansoprazole on Elderly Patients with Chronic Atrophic Gastritis and Its Influence on Gastric Function - Zhang Wanglai; Shao Huang; Tao Yunsheng; Li Meng; Zhou Zelin; Wu Funing (Guoji laonian yixue zazhi)
Objective To explore the effect of quadruple regimen with Lansoprazole in elderly patients with chronic atrophic gastritis and its influence on gastric function. Methods A total of 82 elderly patients with Helicobacter pylori(Hp)-positive chronic atrophic gastritis were enrolled as the research objects between January 2021 and December 2023. They were randomly divided into an observation group and a control group according to random number table, 54 cases in each group. The control group was treated with routine quadruple therapy (Omeprazole+Amoxicillin+Clarithromycin+Colloidal Bismuth Pectin), while the observation group was treated with quadruple regimen containing Lansoprazole (Lansoprazole + Amoxicillin + Clarithromycin + Colloidal Bismuth Pectin). The clinical curative effect, Hp eradication rate, gastric function indexes ［pepsinogen(PG-) Ⅰ, PG-Ⅱ, and gastrin(G)-17］, gastric mucosal recovery indexes ［epidermal growth factor (EGF), nitric oxide (NO)］, inflammatory indexes ［interleukin(IL)-6, IL-12, tumor necrosis factor(TNF)-α］ and adverse reactions were compared between the two groups. Results The total effective rate and Hp eradication rate in the observation group were higher than those in the control group (P<0.05). After treatment, levels of peripheral blood PG-Ⅰ, PG-Ⅱ, G-17, EGF and NO in observation group were higher than those in control group (P<0.05), and levels of IL-6, IL-12 and TNF-α were lower than those in control group (P<0.05). There was no significant difference in total incidence on adverse reactions between the two groups (P>0.05). Conclusion The curative effect of quadruple regimen with Lansoprazole is significant in elderly patients with Hp-positive chronic atrophic gastritis, which can effectively accelerate the recovery of gastric mucosa, improve gastric function and reduce inflammatory response.